2005
DOI: 10.1163/156856005774423764
|View full text |Cite
|
Sign up to set email alerts
|

Participation of vanilloid/capsaicin receptors, calcitonin-gene-related peptide and substance P in gastric protection of omeprazole and omeprazole-like compounds

Abstract: The effects of omeprazole and different omeprazole-like compounds, associated with anti-ischaemic, antioxidant and poly(adenosine-diphosphate-ribose) polymerase (PARP) inhibitory properties, on the gastric acid secretion (4 h pylorus-ligated) and indomethacin-induced gastric mucosal damage connected with the specific immunohistochemical distribution of TRPV1, CRGP and SP during the effects of these compounds, were studied. The observations were carried out in CFY-strain rats (180-210 g), according to the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This second messenger works intensively for repair. So, acute enhancement of cyclic AMP (20 min) by exposure of cyclic AMP agonist produced a sensitization of rat sensory neurons and a release of immunoreactive substance P, which (such as the cyclic AMP) produces protection [668,866,364] and excites neural cells. At the same time, long-term exposure of the agonist does not appear to downregulate its ability to augment substance P release, to increase cyclic AMP production or to be sensitized [147].…”
Section: Protection Through a Detoured Routementioning
confidence: 99%
See 1 more Smart Citation
“…This second messenger works intensively for repair. So, acute enhancement of cyclic AMP (20 min) by exposure of cyclic AMP agonist produced a sensitization of rat sensory neurons and a release of immunoreactive substance P, which (such as the cyclic AMP) produces protection [668,866,364] and excites neural cells. At the same time, long-term exposure of the agonist does not appear to downregulate its ability to augment substance P release, to increase cyclic AMP production or to be sensitized [147].…”
Section: Protection Through a Detoured Routementioning
confidence: 99%
“…Serotonin ameliorates cellular damage [1370,1107], plays a pivotal role in the homeostasis of neural tissue [69] and stimulates cell proliferation. Peptide neurotransmitter substance P also protects neurons [866,364]. Motivationally relevant substances, neuropeptides and neurohormones also affect the processes of neuronal damage, when they act on behavior 1 .…”
Section: 1mentioning
confidence: 99%
“…Mozsik et al [117] suggested participation of vanilloid/capsaicin receptors, CGRP and substance P in gastric protection of omeprazole and omeprazole-like compounds.…”
Section: Role Of Capsaicin Sensitive Afferent Nerves In Action Of Permentioning
confidence: 99%
“…In our further research significant changes were observed in the immunhistological distribution of TRPV1, CGRP and SP in patients with chronic H. pylori positive gastritis and in histological healthy subjects but no change could be detected between the patients suffered from chronic gastritis without or with H. pylori infection . The effect of omeprazole and omeprazole-like compounds could also be demonstrated in the gastric mucosa of rats by the changes of the TRPV1, CGRP and SP immunodistribution and by the reduction of number and severity of gastric mucosal lesions (Mózsik et al, 2005b).…”
Section: Introductionmentioning
confidence: 98%